Photonics as a useful tool from medicine to gas supply systems - Karpierz, Miroslaw A. (Photonics Letters of Poland, 2011)
<span style="font-size: 8.0pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">A brief editorial overview of the current issue is presented. This number of Photonics Letters of Poland contains 12 regularly submitted letters showing wide applications of optical and photonic methods.